2017
DOI: 10.1051/0004-6361/201628916
|View full text |Cite
|
Sign up to set email alerts
|

Herschel/HIFI spectral line survey of the Orion Bar

Abstract: Context. Photon dominated regions (PDRs) are interfaces between the mainly ionized and mainly molecular material around young massive stars. Analysis of the physical and chemical structure of such regions traces the impact of far-ultraviolet radiation of young massive stars on their environment. Aims. We present results on the physical and chemical structure of the prototypical high UV-illumination edge-on Orion Bar PDR from an unbiased spectral line survey with a wide spectral coverage which includes lines of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
37
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 58 publications
7
37
0
Order By: Relevance
“…They also reproduce (±3 K) the T rot inferred from the rotational population diagrams for a 10 -wide filament (see Table B.1). For H 13 CO + , HOC + , and SO + , we obtain n(H 2 ) 10 5 cm −3 , n(e − ) = 10 cm −3 , and T k 200 K. These conditions agree with those inferred by Nagy et al (2017) for the H 12 CO + rotationally excited emission (J = 6−5 to 11−10) observed by Herschel/HIFI.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…They also reproduce (±3 K) the T rot inferred from the rotational population diagrams for a 10 -wide filament (see Table B.1). For H 13 CO + , HOC + , and SO + , we obtain n(H 2 ) 10 5 cm −3 , n(e − ) = 10 cm −3 , and T k 200 K. These conditions agree with those inferred by Nagy et al (2017) for the H 12 CO + rotationally excited emission (J = 6−5 to 11−10) observed by Herschel/HIFI.…”
Section: Discussionsupporting
confidence: 87%
“…Herschel allowed the detection of OH, CH + , and SH + emission toward dense PDRs (Goicoechea et al 2011;Nagy et al 2013Nagy et al , 2017Parikka et al 2017). Unfortunately, the limited size of the space telescope did not permit us to resolve the ∆A V 1 mag extent of the DF (a few arcsec for the closest PDRs).…”
Section: Introductionmentioning
confidence: 99%
“…Individual analyses of the full spectra have been reported for OrionKL (Crockett et al 2014), OrionS (Tahani 2013;Tahani et al 2016), the Orion Bar (Nagy et al 2017), and SgrB2(N) + at 692GHz, J=7-6 by OT1_mgerin_4 in observations targeting CI at 809GHz, and J=8-7 by OT1_cvastel_2 in observations targeting HDO at 919GHz. Observations of these three transitions utilized the WBS, and were made in DBS mode.…”
Section: Observationsmentioning
confidence: 99%
“…Similarly, a complex chemistry is also found towards disks (e.g., Öberg et al 2015;Guzmán et al 2015), shocked gas (e.g., Codella et al 2010;Sugimura et al 2011) and photon-dominated regions (e.g., Treviño-Morales et al 2014Nagy et al 2017). In extragalactic astronomy, recent observations reach good enough sensitivities to detect an increasing number of spectral line features in the central regions of many galaxies (e.g., González-Alfonso et al 2004;Martín et al 2006Martín et al , 2011Aladro et al 2011;Rangwala et al 2011;Muller et al 2011Muller et al , 2014Meier et al 2015), and it is expected that individual hot molecular cores will soon be detected in other galaxies (see e.g., Shimonishi et al 2016).…”
Section: Introductionmentioning
confidence: 95%